2013
DOI: 10.1002/term.1667
|View full text |Cite
|
Sign up to set email alerts
|

A papain-induced disc degeneration model for the assessment of thermo-reversible hydrogel-cells therapeutic approach

Abstract: Nucleus pulposus (NP) regeneration by the application of injectable cell-embedded hydrogels is an appealing approach for tissue engineering. We investigated a thermo-reversible hydrogel (TR-HG), based on a modified polysaccharide with a thermo-reversible polyamide [poly(N-isopropylacrylamide), pNIPAM], which is made to behave as a liquid at room temperature and hardens at > 32 °C. In order to test the hydrogel, a papain-induced bovine caudal disc degeneration model (PDDM), creating a cavity in the NP, was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Bovine caudal IVDs were used because of their large size and similarities with human lumbar IVDs (Demers et al ., 2004; Oshima et al ., 1993). In addition, bovine and other large animal IVDs are readily available and have been thoroughly characterised biomechanically and in organ culture studies (Chan et al ., 2011; Gantenbein et al ., 2006; Haglund et al ., 2011; Illien-Junger et al ., 2012; Junger et al ., 2009; Korecki et al ., 2008a; Korecki et al ., 2008b; Lee et al ., 2006; Malonzo et al ., 2013; Michalek and Iatridis, 2012; Ohshima et al ., 1995; Paul et al ., 2012; Walter et al ., 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Bovine caudal IVDs were used because of their large size and similarities with human lumbar IVDs (Demers et al ., 2004; Oshima et al ., 1993). In addition, bovine and other large animal IVDs are readily available and have been thoroughly characterised biomechanically and in organ culture studies (Chan et al ., 2011; Gantenbein et al ., 2006; Haglund et al ., 2011; Illien-Junger et al ., 2012; Junger et al ., 2009; Korecki et al ., 2008a; Korecki et al ., 2008b; Lee et al ., 2006; Malonzo et al ., 2013; Michalek and Iatridis, 2012; Ohshima et al ., 1995; Paul et al ., 2012; Walter et al ., 2011). …”
Section: Methodsmentioning
confidence: 99%
“…This specific gel has been developed for future minimally invasive treatments allowing injection of the material followed by in situ gelation. So far, the HA-pNIPAM gel has been studied for possible use in nucleus pulposus tissue regeneration (Peroglio et al, 2012;Malonzo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of GDF-5 seems to increase cell activity (Figure 2) and the rate of PEG hydrogel degradation as shown by reduced amount of PEG hydrogel in histological evaluation (Figure 4). In recent findings by our group we could demonstrate that the IVD environment along with mechanical loading represents a major "discogenic" differentiation stimulus for hMSC; this stimulus being much stronger than the pre-conditioning in presence of 100ng/ Ml GDF5 added to the media [35]. Several studies have shown that mechanical loading applied on stem cells might improve the outcome of chondrogenesis of stem cells [18,19,36].…”
Section: Gdf5 and Mechanical Loading Stimulationsmentioning
confidence: 86%